(Invited) Determination of Effective Reaction Area in a Mixed-Conducting SOFC Cathode. (13th April 2015) - Amezawa, Koji; Fujimaki, Yoshinobu; Nakamura, Takashi; Bagarinao, Katherine Develos-; Yamaji, Katsuhiro; Nitta, Kiyofumi; Terada, Yasuko; Iguchi, Fumitada; Yashiro, Keiji; Yugami, Hiroo; Kawada, Tatsuya
Abstract : For the quantitative determination of the effective reaction area in an SOFC cathode, a new type of model patterned electrode was proposed and fabricated with La0.6 Sr0.4 CoO3- δ (LSC). In situ micro X-ray absorption spectroscopy (XAS) measurements were performed in 1 bar of p (O2 ) at 973 K under open circuit and cathodic polarization. Absorption spectra were taken at different positions with the position resolution of less than 1 μm. The increase in the absorbance, i.e. the decrease in the oxygen potential, was observed near the electrod/electrolyte interface, when the electrode was cathodically polarized. The characteristic length of the effective reaction area for the patterned LSC electrode was estimated approximately 20 μm from the interface. Electrochemical impedance spectroscopy (EIS) measurements were also carried out with the patterned LSC electrode. The characteristic length of the effective reaction area estimated by EIS was close to one by XAS.